Análisis de los factores de la enfermedad renal crónica y su relación en la hemodialisis de los pacientes que acuden a la clínica farmadial del cantón Balzar, año 2014 - Mera Jacho, Isela georgina (2015)
The study in the Clinical Farmadial Canton Balzar lasted ninety days, whose main objectives were to determine the direct and indirect factors influencing chronic kidney disease, develop and implement a training program on prevention and management of kidney diseases chronic patients who come to the institution in order to slow the progression of this disease that affects the tenth of the world's population. Chronic kidney disease (CKD) is the slow loss of kidney function over time, the main job of the kidneys is to remove wastes and excess water from the body, as the disease progresses and the kidneys are no longer the ability to remove enough wastes and excess fluid, then you need hemodialysis or kidney transplantation. According to the evaluations obtained from the training, 90% of respondents attended training ignorance, where 85 % were able to learn about chronic kidney disease, because 90% understood the management and control of medicine with their nutrition and 76 % of family understood about the causes and effects of this disease, and how can contribute positively to their families affected, which in their entirety are willing to contribute in their food, and wish to receive more information about disease. It is necessary that both the families, government and society in general become conscious of people with chronic kidney disease and mechanisms that allow them to reduce complications during the hemodialysis to improve their quality of life and allow time enjoy and benefit is sought which diminishes life